2009
DOI: 10.1007/s10230-009-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hydraulic Residence Times in Several UK Mine Water Treatment Systems and their Relationship to Iron Removal

Abstract: In the UK, the Coal Authority has more than 40 mine water treatment systems, most of which are wetland systems with settlement lagoon pretreatment. The purpose of treatment in wetlands is the oxidation of ferrous to ferric iron and the subsequent hydrolysis and precipitation of ferric hydroxide within the wetland. It is generally accepted (Hedin et al., Passive treatment of coal mine drainage, 1994, p 35; Skousen and Ziemkiewicz, Acid mine drainage control and treatment, 1996, p 362; Younger et al., Mine wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Badly maintained wetlands with spatially irregular vegetation distribution or silting up can have opposite effects, such as flow channelling or plugging (Brix 1994;Jadhav and Buchberger 1995;Klerk et al 2016;Persson et al 1999;Wahl et al 2012). Field tracer tests of various settling ponds and wetlands in UK passive mine water treatment systems showed better hydraulic efficiency for wetlands, whereas the effective volume of settling ponds was often considerably reduced due to dispersed flow, poor mixing, and short-circuiting (Kruse et al 2009;Kusin et al 2010;Sapsford 2013).…”
Section: Hydraulic Effectsmentioning
confidence: 99%
“…Badly maintained wetlands with spatially irregular vegetation distribution or silting up can have opposite effects, such as flow channelling or plugging (Brix 1994;Jadhav and Buchberger 1995;Klerk et al 2016;Persson et al 1999;Wahl et al 2012). Field tracer tests of various settling ponds and wetlands in UK passive mine water treatment systems showed better hydraulic efficiency for wetlands, whereas the effective volume of settling ponds was often considerably reduced due to dispersed flow, poor mixing, and short-circuiting (Kruse et al 2009;Kusin et al 2010;Sapsford 2013).…”
Section: Hydraulic Effectsmentioning
confidence: 99%
“…As the processes involved in the remediation of net-alkaline and netacidic metal polluted water in aerobic wetlands and lagoons are very similar, it was decided to use both of them to compare with the results obtained in the NFOL in Monte Romero (Table 3). As can be observed, the highest Fe removal reported in lagoons treating net-alkaline waters is 26 g/m 2 /day (Hedin, 2008;Kruse et al, 2009) while aerobic wetlands treating net-acidic waters only achieved 6 g/m 2 /day (Whitehead et al, 2005). The NFOL pretreatment showed a mean Fe removal as high as 100 g/m 2 /day over the study period, 4 to 16 times higher than the Fe removal observed in other conventional treatments.…”
Section: Nfol Performancementioning
confidence: 72%
“…Goulet et al 2001;Kruse et al 2009). Therefore a higher removal of iron would be anticipated for system with a more hydraulically efficient performance.…”
Section: Relationship Between Hydraulic Characteristics and Iron Removalmentioning
confidence: 97%
“…longer hydraulic residence time) should be reflected in effective treatment performance. However, assessment of actual residence time within the UK coal mine water treatment systems has not been widely investigated (Kruse et al 2007). It is therefore the aim of this study to assess the effect of system hydraulic efficiency (i.e.…”
Section: Introductionmentioning
confidence: 99%